SINGLE STAGE HYPOSPADIAS REPAIR IN PRIMARY CASES AND THEIR PATIENT RELATED OUTCOMES – TERTIARY CARE CENTER EXPERIENCE - Mukesh Chandra Arya; Ram Naresh Daga; Ajay Gandhi; Ankur Singhal; Yogendra Shyoran; Medhanshu Kumar (Jurnal Urologi Indonesia, 2022)
Objective: This study aims to study whether hypospadias repair in primary cases can be done in a single stage. We present patients’ perspective and their outcomes in 268 primary hypospadias cases among which around 90% of patients (n=240) had their hypospadias surgery after recommended age of repair (18 months).  All primary cases were managed in a single stage. Material & Methods: From January 2010 – December 2019, 377 patients were included and outcomes were documented. Patients with prior hypospadias with complications (n=48), chordee without hypospadias (n=16), isolated penile torsion (n=12), and 33 patients who were lost to follow-up were excluded. The age at surgery, location of the meatus, chordee, associated anomalies, techniques used for correction,  postoperative complications with overall success rate and patient related outcomes were evaluated. Results: After orthoplasty, distal hypospadias was seen in 59% (n=158), middle in 22.8 % (n=61) & proximal in 13.1% (n=35) patients. Fourteen patients (5.2%) had penoscrotal transposition. Chordee was present in 71.2% (n=192) cases. Urethral closure was done using TIP alone in 18 cases, TIP, and spongioplasty (n=233). The success rate of one-stage surgery was 73.5% in our series which correlated with PRO with high significance. Conclusion: The rate of complications increased with the length of urethral tube reconstruction. Hypospadias fistula was the most common, followed by glanular dehiscence. The use of the TIP in primary repairs, spongioplasty & additional buffering layers reduced the complication rates. Patients can have acceptable residual chordee and torsion and their surgical results correlated well with patient related outcomes(PRO).